Influence of white‐tailed deer population density on vegetation standing crop in a semiarid environment. Issue 3 (April 2015) - Crider, Brandi L.; Fulbright, Timothy E.; Hewitt, David G.; Deyoung, Charles A.; Grahmann, Eric D.; Priesmeyer, Whitney J.; Wester, David B.; Echols, Kim N.; Draeger, Don
ABSTRACT: Diet selection theory predicts that selective foraging by white‐tailed deer ( Odocoileus virginianus ) may reduce palatable and nutritious plants when high‐quality food resources are available or deer densities are high. Our objectives were to determine if providing a high‐quality food resource ad libitum and increasing deer densities 1) reduced standing crop and nutritional quality of forbs and 2) altered standing crop and nutritional quality of grasses and shrubs. We used 6 81‐ha controlled‐density enclosures on each of 2 study sites in southern Texas with deer densities considered low (12 deer/km 2 ), medium (31 deer/km 2 ), and high (50 deer/km 2 ) relative to the range of population estimates for white‐tailed deer in the Rio Grande Plains of Texas. For each pair of enclosures with the same deer density at each study site, we provided white‐tailed deer in 1 enclosure high‐quality pelletized feed ad libitum and did not provide feed (control) in the other enclosure. During spring and summer 2004–2012, we estimated standing crop of forage in 40 0.25‐m 2  × 1.5‐m volumetric plots/enclosure and we harvested 20 randomly selected plots/enclosure, which we dried to convert wet mass estimates to dry mass. Availability of high‐quality pelletized food and deer density did not affect ( P  ≥ 0.392) forb standing crop during spring and summer. Forb, browse, and grass standing crop and nutritional quality varied ( P  < 0.001) with precipitation among years. Enclosures with low deer densities had lower forb crude protein than those with higher densities ( P  < 0.034) during summer in drought years (2006, 2009, and 2011). Enclosures with high‐quality pelletized food tended to have lower browse crude protein than controls (sampling date × feeding treatment interaction, P  = 0.051) in spring during 2006 and 2007. Variable and limited rainfall had a more pronounced effect on variation in vegetation standing crop than white‐tailed deer foraging regardless of food resource availability or deer density. Vegetation responses were more complex than can be predicted by traditional theory on diet selection in part because of the pronounced effect of variation in rainfall on vegetation standing crop. © 2015 The Wildlife Society.